Penetrating Keratoplasty – Indications in a tertiary care center in Nepal (Nepalese Journal of Ophthalmology, 2020)
Introduction: Penetrating keratoplasty has become one of the most commonly performed transplant procedures where full thickness diseased host corneal tissue is replaced with healthy donor corneal tissue. Aims of penetrating keratoplasty include improvement in visual acuity, removal of infectious load, alleviate pain or even to simply save the anatomy of the eye. Visual improvement and removal of infection is the prime objective of majority of corneal grafts. The objective of the study was to evaluate various current indications of penetrating keratoplasty in central Nepal and its difference from the developed world.Material and methods: A hospital based study of 36 patients who underwent penetrating keratoplasty between January 2014 and June 2015 was carried out at B.P. Koirala Centre for ophthalmic studies. Following clinical examination and investigations, surgical intervention was done when required. The patient data were recorded and followed up. Indication for surgery, investigations and demographic profile were assessed.Results: Mean recipient age was 46.56 years (+/- 16.02 years). The male: female ratio was 1.57:1. The most common indication for penetrating keratoplasty was infectious keratitis (44.44%), followed by corneal opacity or scarring (30.56 %), re-grafts (13.89%),bullous keratopathy (2.78%), keratoconus (2.78%) and others (2.78%)Conclusion: Though corneal diseases and indications for transplant surgery in developing countries are different from those in the western world, penetrating keratoplasty has emerged as one of the most successful way to reduce corneal blindness and to restore vision.